Sistem Informasi Pencatatan Surat Masuk dan Surat Keluar Berbasis Website Menggunakan Metode Waterfall - Arijal Bela Praja; Darmansah Darmansah; Sena Wijayanto (Universitas Budi Darma, 2022)
Sokaraja Lor is a village located in Sokaraja Subdistrict, Banyumas Regency, Central Java Province led directly by the Village Chief. The Village Head is also assisted by the village device consisting of the Village Secretary, Head of Affairs, and Section Head with duties in accordance with their respective fields. As one of the elements of government organizers, the village government has a duty to organize government affairs, community, and village development. Office activities or work related to the management of letters, storage, and documents are called archiving. Recording of incoming and outgoing mail archives at Sokaraja Lor Village Office is still done manually, which is recorded in the ledger and then stored in the storage cabinet. However, stored mail archives are sometimes lost because the borrowed letters are not recorded by the officer. The purpose of this research is to apply the management of mail archives from manual systems into website-based information systems by utilizing information technology to facilitate and assist the work in managing, searching, or inputting. The method used is the waterfall, which is also called a linear sequential model (sequential linear) or classic life cycle. The results of this study are a website system that is expected to improve administrative performance in terms of managing incoming and outgoing mail so that the process of filing letters and mail search becomes easier and faster.